2016
DOI: 10.12714/egejfas.2016.33.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Yaz aylarında Batı Anadolu’nun bazı dağ göllerinin (denizli-muğla) fitoplankton kompozisyonu ve trofik durum indeksi değerleri

Abstract: Sonuç olarak, göllerin fitoplankton kompozisyonu ve diğer bazı ekolojik değerleri, inceleme yapılan göllerin verimlilik durumunun oligotrofik olduğunu göstermektedir. Bu çalışmada, Türkiye'nin dağ göllerinin fitoplankton kompozisyonu ve limnolojisi hakkındaki bilgilere katkılar sağlanması amaçlamıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The TSI index results showed that Lake Bafa was from the limiting mesotrophic to slightly eutrophic. Sömek and Ustaoğlu (2016) stated that oligotrophic and mesotrophic indicatör species are found together in the phytoplankton composition of Saklıgöl, Karagöl, Gökçeova Pond and Kartal Lake, and considering the TSI values, the productivity status of the studied lakes is still oligotrophic but has a transition trend towards mesotrophic state. According to Akçaalan et al (2007), in the research carried out in Sapanca Lake, which is an oligo-mesotrophic lake, diatom was reported to be predominantly found during the research period.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The TSI index results showed that Lake Bafa was from the limiting mesotrophic to slightly eutrophic. Sömek and Ustaoğlu (2016) stated that oligotrophic and mesotrophic indicatör species are found together in the phytoplankton composition of Saklıgöl, Karagöl, Gökçeova Pond and Kartal Lake, and considering the TSI values, the productivity status of the studied lakes is still oligotrophic but has a transition trend towards mesotrophic state. According to Akçaalan et al (2007), in the research carried out in Sapanca Lake, which is an oligo-mesotrophic lake, diatom was reported to be predominantly found during the research period.…”
Section: Discussionmentioning
confidence: 91%
“…After the classification of collected samples, Cyanophyceae (11.2%), Bacillariophyceae (49.2%), Chlorophyceae (23.8%), Xanthophyceae (1.5%), Euglenophyceae (11.2%) and Dinophyceae (3.1%) classis were determined. Cyanobacteria members were commonly detected in eutrophic lakes in our country (Cirik-Altındağ, 1982;Sömek and Balık, 2009) and they had excessive growth in eutrophic lakes rich in nutrients in summer months (Vaitomaa, 2006). In this study, a few taxa (Cylindrospermopsis raciborskii, Lyngbya sp.…”
Section: Discussionmentioning
confidence: 99%
“…(Dullinger et al, 2012). For this reason, these ecosystems are represented by relatively low numbers of endemic or adapted species to extreme environmental conditions (Galas, 2004;Krno et al, 2006;Sömek & Ustaoğlu, 2016). In this respect, these lakes are reference points in testing the effects of environmental degradation on the ecosystem (Galas, 2004;Taşdemir & Ustaoğlu, 2016).…”
Section: Introductionmentioning
confidence: 99%